A review of global coagulation assays — Is there a role in thrombosis risk prediction?. Issue 179 (July 2019) - Lim, Hui Yin; O'Malley, Cindy; Donnan, Geoffrey; Nandurkar, Harshal; Ho, Prahlad
Abstract: Normal haemostasis requires maintenance of a careful equilibrium between the necessity to clot when bleeding and the retention of fluid phase at all other times. Disruption of this equilibrium can result in catastrophic outcomes, e.g. acute myocardial infarction and pulmonary embolism. However, despite the significant therapeutic advances in cardiovascular medicine over recent years, our ability to provide an accurate cardiovascular risk assessment remains an unmet need. Routine coagulation testing is not a useful reflection of haemostasis and cannot be reliably used to predict bleeding and thrombosis risks. Global coagulation assays such as viscoelastic testing, thrombin and fibrin generation have been proposed as better measures of the haemostatic function. These assays, particularly viscoelastic testing, have been increasingly used to assess bleeding risks and guide blood product replacement in trauma and massive transfusion settings. However, the role of these assays in thrombosis is less well-defined but given the complexities of the coagulation system, these global coagulation assays when used in combination may provide a better assessment of cardiovascular and thrombosis risk at an individual level. Hence, we explore the role of some of the currently available global coagulation assays – the viscoelastic, thrombin generation and fibrin generation tests – and provide a review of the literature of the current evidence for these assays specifically in the field of venous thromboembolism and cardiovascular diseases. Highlights: There is no biomarker currently available to quantify thrombotic risk. Data regarding use of global coagulation assays in thrombosis is emerging. Further studies evaluating clinical outcomes using these assays are required.